Designing Instructional Media for Islamic Boarding Schools: A Systematic Literature Review in ICT-Based ELT - Triana, Devi; Syahmiarni, Syahmiarni; Sesmiarni, Zulfani; Syafitri, Widya (Ahlussunnah: Journal of Islamic Education, 2025)
The rapid integration of Information and Communication Technology (ICT) in English Language Teaching (ELT) highlights the necessity for instructional media that are contextually relevant to diverse educational settings, including Islamic boarding schools (pesantren). This study aims to systematically review existing empirical research focusing on the design and implementation of ICT-based instructional media for ELT in pesantren environments, particularly those adopting instructional frameworks such as ADDIE and TPACK. A systematic literature review method was employed following the PRISMA protocol, examining 25 SINTA 4 indexed articles published between 2019–2025. Data extraction and thematic analysis were conducted to categorize findings based on types of media developed, pedagogical frameworks applied, student learning outcomes, and contextual challenges encountered in pesantren settings. The results reveal that most studies successfully implemented ICT-based media such as mobile learning applications, digital games, and multimedia modules, which demonstrated positive impacts on students’ English proficiency, motivation, and autonomous learning. However, challenges remain, including limited digital infrastructure, teacher ICT competence, and the need for alignment between technological tools and Islamic cultural values. This review suggests that future research should enhance technology acceptance models among pesantren educators and strengthen ICT professional development to optimize ELT innovation in Islamic boarding schools. The study contributes both theoretically and practically by providing updated insights and identifying research gaps in ICT-based media design within pesantren contexts.